The Political Economy of the United States in the Era of Hatred and Partisan Polarization - Owoye, Oluwole (Advances in Social Sciences Research Journal, 2018)
This paper uses conceptual economics to analyze the consequences of the rising racial-gender hatred and partisan polarization on the political economy of the United States. The upsurge in hate crimes nationwide is due to the politicians’ peddling of hate-creating stories and false narratives. This paper identifies and discusses the three interdependent institutions through which hatred and partisan polarization could destabilize the political economy; and tests whether the increasing racial-gender hate crimes, partisan polarization, and government shutdowns have adverse effects. The statistical tests confirm the research hypotheses about the rising racial-gender hate crimes; and that partisan polarization and government shutdowns have negative effects on Congressional productivity in the United States.